Exoskeletons for the rehabilitation of temporomandibular disorders: a comprehensive review - Müller, Paul-Otto; Sader, Robert; von Stryk, Oskar (Frontiers in Robotics and AI, 2025)
Despite the many technological advancements in exoskeletons for the rehabilitation of lower or upper limbs, there has been limited exploration of their application in treating temporomandibular disorders, a set of musculoskeletal and neuromuscular conditions affecting the masticatory system. By collecting data, implementing assisting and resisting training routines, and encouraging active patient engagement, exoskeletons could provide controlled and individualized exercise with flexibility in time and location to aid in the recovery or improvement of jaw mobility and function. Thus, they might offer a valuable alternative or complement to conservative physiotherapy. In this context, the review aims to draw attention to rehabilitating temporomandibular disorders with the help of exoskeletons by looking at the advantages and opportunities these devices potentially provide. After stating the requirements and resulting scientific challenges in various fields and discussing the state of the art, existing research gaps and deficiencies will be discussed, highlighting areas where further research and development is needed.